Analisis Yuridis terhadap Pelaku Penyebaran Konten Bermuatan Seksual di Media Sosial - Orli Zafirah; Sanusi Sanusi (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the regulation and resolution of the crime of distributing sexually charged content on social media. The method used is normative juridical, supported by interview data. The results show that the regulation of this act has been accommodated in the Electronic Information and Transactions Law, the Sexual Violence Crime Law, the Pornography Law and the Criminal Code, so there is no normative gap, although there are still overlapping regulations. The resolution is carried out through preventive and repressive efforts with an emphasis on victim protection and recovery. Strengthening victim assistance and increasing public awareness regarding digital security is needed.